Fantastic voyage [videorecording (DVD)] - Bixby, Jerome, 1923-1998; Klement, Otto; Fleischer, Richard; Boyd, Stephen, 1931-1977; Welch, Raquel; O'Brien, Edmond, 1915-1985; Pleasence, Donald; O'Connell, Arthur, 1908-1981; Redfield, William, 1927-1976; Kennedy, Arthur, 1914-1990; Del Val, Jean, 1891-1975; Coe, Barry, 1934-2019-; et al. (20th Century Fox Home Entertainment, 2007)
An elite team of medical and scientific specialists race to save a top government scientist who is suffering from blood clot on the brain. Their mission is to be reduced along with their submarine-like craft to microscope size, enter the bloodstream of the ailing scientist, and journey to the brain to perform an emergency procedure. With only sixty minutes to complete their mission, the scientists find themselves fighting off an attack by white corpuscles, caught in a tornado-like storm in the lungs, and struggling to surviv sabotage from one of their own.